Model Pentahelix dalam Pengembangan Usaha Rengginang di Kecamatan Ciparay Kabupaten Bandung - Awaludin, Mochamad Bashiir; Trimo, Lucyana; Sendjadja, Tuhpawana Priatna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The rengginang business in Ciparay Sub-district, Bandung Regency, holds significant economic potential as part of the MSME sector, yet faces various challenges such as limited capital, lack of management training, fluctuating raw material prices, and difficulties accessing modern markets, exacerbated by the impact of the COVID-19 pandemic. This study aims to identify the constraints, expectations, and solutions for developing the rengginang business through the Pentahelix approach, which involves collaboration among academics, government, business, community, and media. Employing a qualitative method with in-depth interviews of 104 rengginang entrepreneurs, field observations, and thematic analysis, the study found that the main constraints include limited capital, complex licensing processes, manual bookkeeping, dependence on weather, and weak digital marketing. Proposed solutions encompass capital assistance, management and digital marketing training, simplified licensing, and the establishment of an entrepreneur community to strengthen networks and innovation. The Pentahelix approach is expected to create synergy among stakeholders to enhance productivity and welfare of rengginang entrepreneurs sustainably.